Ballistic and thermomechanical characterisation of hybrid rocket fuels - Md. Zishan Akhter (2018)
Hybrid rockets have been intense topic of research for their safety and environmental advantages over the conventional rocket systems. The development of hybrid rocket started with high-density long-chained polymers such as Hydroxyl-Terminated Poly-Butadiene (HTPB), but there were concerns regarding low regression rates. Lately, Paraffin-based fuels were tested and higher regression rates (3-4 times) were achieved. However, the melt flow effect associated with liquefying fuels, reduces the combustion efficiency of the system. Therefore, a trade-off needs to be done to achieve the desired propulsive performance. This thesis developed advanced hybrid rocket fuels, having tunable thermomechanical and ballistic properties. Blend of Paraffin Wax and Hydroxyl-Terminated Poly-Butadiene (HTPB), doped with light metal hydrides - Magnesium hydride (MgH2) and Lithium aluminium hydride (LiAlH4) were formulated in several compositions to achieve higher average regression rates and improved performance. The effect of binders and additives on the change in the heat of gasification and eventually the solid-fuel regression rate was investigated. The metal hydrides were found to be evenly dispersed in the fuel-matrix. It was observed that MgH2-doped fuel exhibited liquid-like behaviour in contrast to the LiA1H4-doped samples. Thus, the latter ones exhibited stronger cross-linkages and therefore, can withstand greater thermal and inertial flight loads. Ballistic characterisation of the doped fuels revealed enhancement in fuel regression behaviour up to 733%, as compared to HTPB. LiAlH4-doped fuels demonstrated relatively higher regression as compared to the MgH2-doped counterparts. Future work may include mechanical characterisation of the developed fuels at varied thermal and strain loads, to couple with the obtained thermomechanical and ballistics data. These advanced fuels shall eventually be subjected to scale-up tests to demonstrate their applicability in the Space industry.